Antimicrobial Activity of Phoebe lanceolata and Stephania glabra; Preliminary Screening Studies (Journal of Scientific Research, 2009)
Ethanolic extracts of Phoebe lanceolata stem bark and Stephania glabra tubers were evaluated for their antibacterial and antifungal activities against five bacterial species, Staphylococcus aureus (along with ten hospital strains), Staphylococcus mutans, Staphylococcus epidermidis, Escherichia coli, Klebsiella pneumoniae and six fungal species Aspergillus niger, Aspergillus fumigatus, Penicillum citranum, Microsporum gypseum, Microsporum canis, Trichophyton rubrum, obtained from different culture media. The plants/parts extracts were found active against most of the tested microorganism with MIC range of 50-100µg/ml. The MIC was taken at the lower concentration where inhibition ceased. Novobiocin (15 µg/ml) and erythromycin (15 µg/ml) were used as positive controls for bacterial and fungus species respectively.  Keywords:Antimicrobial activity; Streptococcus mutans; Klebsiella pneumoniae; Microsporum gypseum; Nutrient and Sabouraud’s dextrose agar medium. © 2009 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. DOI: 10.3329/jsr.v1i3.2423               J. Sci. Res. 1 (3), 662-666 (2009)